2021
DOI: 10.1186/s12884-021-04080-1
|View full text |Cite
|
Sign up to set email alerts
|

Continuum of maternity care in Zambia: a national representative survey

Abstract: Background Globally, over half of maternal deaths are related to pregnancy-related complications. Provision of a continuum of care during pregnancy, childbirth and the postnatal period results in reduced maternal and neonatal morbidity and mortality. Hence this study determined the prevalence of the continuum of care and its determinants among women in Zambia. Methods We used weighted data from the Zambian Demographic and Health Survey (ZDHS) of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 36 publications
4
50
6
Order By: Relevance
“…This is similar to that of other countries in the region, and has not changed much since the previous survey done in 2011 ( S1 Table ). Similar studies based on secondary data from nationally representative samples have reported a 9.1% level of coverage in Ethiopia [ 35 ], and 38% level of coverage in Zambia [ 41 ]. This may be explained by differences in the levels of gross domestic product (GDP), while Uganda is in the low income category, both Kenya and Zambia have attained middle income status according to the World Bank rankings [ 42 ].…”
Section: Discussionmentioning
confidence: 59%
“…This is similar to that of other countries in the region, and has not changed much since the previous survey done in 2011 ( S1 Table ). Similar studies based on secondary data from nationally representative samples have reported a 9.1% level of coverage in Ethiopia [ 35 ], and 38% level of coverage in Zambia [ 41 ]. This may be explained by differences in the levels of gross domestic product (GDP), while Uganda is in the low income category, both Kenya and Zambia have attained middle income status according to the World Bank rankings [ 42 ].…”
Section: Discussionmentioning
confidence: 59%
“…Early initiation of antenatal care (ANC) is highly recommended by the new 2016 World Health Organization (WHO) guidelines [ 1 ]. Accessing ANC services within the first trimester has been associated with better outcomes during the antenatal period, because it allows for timely identification and management of high risk patients [ 2 , 3 ]. Unfortunately, there are large global disparities in ANC utilization, with sub-Saharan Africa and South Asia having the lowest utilization rates [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…ANC is an entry point to the utilization of maternal health services [ 7 ]. Studies have documented that women who initiate ANC early develop confidence in the maternity services and they are more likely to deliver under the care of a skilled birth attendant and also utilize early postnatal care (PNC); practices which have been associated with positive maternal and neonatal outcomes of pregnancy [ 3 , 7 , 8 ]. WHO previously recommended focused ANC Model that emphasized at least four ANC visits for every normal pregnancy [ 9 ], this was modified in 2016 from four to at least eight contacts, with the first contact to be made within the first 12 weeks of gestation [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2019 Sierra Leone Demographic and Health Survey (SLDHS) showed that the maternal mortality ratio (MMR) was 717 deaths per 100,000 live births, meaning for every 1000 live births, about seven women (7.17) died during pregnancy, childbirth or within 6 weeks of childbirth [ 4 ]. This MMR is over 10 times higher than the SDG 3 target of 70 deaths per 100,000 live births by 2030 [ 5 ]. SLDHS further shows that neonatal mortality ratio (NMR) stands at 31 per 1000 live births, down from 39 per 1000 live births in 2013 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the progress has been mainly with skilled antenatal care attendance and facility-based deliveries with little progress regarding PNC utilisation [ 7 , 8 ]. Yet,the immediate postpartum period is critical for the survival of both mothers and newborns because that is when most physiological adaptations occur [ 1 , 5 ]. In this regard, receipt of timely postnatal care (PNC) is widely used to track progress towards national and international maternal child health goals [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%